Slowing things down: taming time in the neoliberal university using social work distance education. Issue 6 (18th August 2018) - Smith, Kristin; Jeffery, Donna; Collins, Kim
Abstract: The neoliberal university is described as a space where there is an ever-present 'scarcity of time' as faculty face increasingly high-paced demands for efficiencies and productivity. By this logic, students are produced as self-enterprising individuals, steeped in the values of competition, and solely invested in enhancing their human capital. Within this context, online education has gained prominence as an alternative to on campus, face-to-face post-secondary education. In this article, we draw on findings from qualitative interviews conducted with social work educators who teach using online-based pedagogy as well as recent graduates who completed their social work education in distance learning programmes. Our research explores how distance education shapes the pace of knowledge production in Canadian Schools of Social Work where a mandate to promote social justice-based professional practices coincides with time constraints associated with neoliberalism. Building on conceptualizations of temporality, we found that when mobilized as a time-saving measure, online programmes can exacerbate the intensified workload for both teachers and students, and they can also limit potential for equity and inclusion in the university. However, when mobilized as a 'time-taming' measure, adequately resourced distance social work education programmes offer possibilities of resistance to pressures faced in post-secondary institutions.